It happened one midnight - DeWylde, Saranna (DeWylde, Saranna. Fairy Godmothers, Inc. (Series), 2022)
"Novelist Juniper Blossom has romance down to a science in her bestselling books. But she's not about to settle for just any man-a happy ending looks different for everyone, and she needs to find the guy whose idea of forever matches her own ... Divorce attorney Tomas Rivera is as proud of Juniper's authorial success as she is, but that doesn't mean he buys into her books' premise. His career is proof enough that true love is the real fairy tale-and everyone knows fairy tales aren't real"--